Comparison of cefotetan and cefoxitin prophylaxis for abdominal and vaginal hysterectomy - Berkeley, A S; Freedman, K S; Ledger, W J; Orr, J W; Benigno, B B; Gordon, S F; McGregor, J A; Galask, R P; Sevin, B U (American journal of obstetrics and gynecology, 1988)
The safety and efficacy of parenteral prophylaxis with either cefotetan or cefoxitin were evaluated in a prospective, randomized study of 355 subjects undergoing abdominal or vaginal hysterectomy. Each subject received either a single 1 gm dose of cefotetan intravenously 30 to 60 minutes before operation or three 2 gm doses of cefoxitin, the first 30 to 60 minutes before operation and subsequent doses 6 and 12 hours later. Prophylaxis was successful in 69 of 70 (98.6%) receiving cefotetan and 32 of 33 (97.0%) receiving cefoxitin who underwent vaginal hysterectomy. Prophylaxis was successful in 160 of 169 (94.7%) receiving cefotetan and in 79 of 83 (95.2%) receiving cefoxitin who underwent abdominal hysterectomy. Both drugs were well tolerated and without serious side effects or complications. On the basis of these findings, we conclude that a single 1 gm dose of cefotetan given before operation is as safe and effective as a multiple-dosing regimen of cefoxitin in subjects undergoing vaginal hysterectomy and in those undergoing abdominal hysterectomy at institutions where prophylaxis is indicated.